Coupling dissolved organic carbon, CO2 and productivity in boreal lakes. (13th March 2017) - Hessen, Dag O.; Håll, Johnny P.; Thrane, Jan‐Erik; Andersen, Tom
Summary: Lakes worldwide are in rapid change because of direct or indirect climate impacts. In boreal areas, the increased concentrations of dissolved organic matter (DOM) are profoundly affecting light climate and productivity in multiple ways. Photochemical and microbial mineralisation of DOM are major sources of CO2 in these lakes. It has been suggested that this CO2 could potentially promote primary production and offset negative impacts of increased light attenuation. A synoptic survey of 76 Scandinavian lakes along gradients of DOM and total phosphorus (TP) revealed a major negative impact of DOM on primary production and algal biomass primarily related to light attenuation, whilst a strong positive impact of TP. The negative impact of DOM on lake productivity is thus partly offset by DOM‐associated P. Concentrations of CO2 did not relate significantly to either production, biomass, or seston stoichiometry, and thus whilst elevated CO2 may promote primary production in more productive lakes, it does not in these CO2 ‐supersaturated boreal lakes. Zooplankton biomass correlated strongly with TP and total algal biomass, less so with primary production, and was negatively related to DOM, likely reflecting the autotroph responses to DOM.